2018
DOI: 10.12688/f1000research.13838.1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a health literacy approach to counselling on the lifestyle of women with gestational diabetes: A clinical trial

Abstract: Background: Gestational diabetes is a common pregnancy disorder that affects the mother’s and neonate’s health. The present study was conducted to investigate the effect of a health literacy approach to counselling on the lifestyle of women with gestational diabetes. The present randomized controlled clinical trial was conducted in 2017 using a parallel design. The subjects included 84 eligible women presenting to Alborz and Kamali Hospitals, Karaj, Iran. Methods: Convenience sampling was first used to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“…The remaining four were quasi-experimental pre-post controlled trials [33,35,42,48]. Studies took place in nine countries -USA [30,31,37,39,40,42,43,45], Australia [35,51,52], Iran [32,34,47], China [41,44], Japan [36,49], Taiwan [48], Niger [38], Germany [50] and Demark [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining four were quasi-experimental pre-post controlled trials [33,35,42,48]. Studies took place in nine countries -USA [30,31,37,39,40,42,43,45], Australia [35,51,52], Iran [32,34,47], China [41,44], Japan [36,49], Taiwan [48], Niger [38], Germany [50] and Demark [33].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Two studies focused on the domain of disease prevention (cancer screening [39] and malaria health literacy [38]), eight focused on healthcare (diabetes [30,37], gestational diabetes [32], breast cancer [36], cardiac conditions [33,34], one or more chronic conditions [35] and people taking two or more medications daily [31]). The remaining 12 studies focused on health promotion with eight focusing on general health promotion [41,42,44,45,48,[50][51][52], two focusing on nutrition [40,43], one on nutrition and physical activity [49] and one on smoking prevention [47].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers in the intervention group participated in 6 HL sessions together with counselling on routine pregnancy care, while the control group received only general counselling and a training package. This trial showed significant differences in mean scores of lifestyle behaviours and health literacy after the intervention between intervention and control groups (Gharachourlo et al, 2018).…”
mentioning
confidence: 77%
“…Gharachourlo et al (2018) [29] 84 Counselling Questionnaire Research findings showed that counselling by midwives can improve MHL.…”
Section: Questionnairementioning
confidence: 99%